HYPERTENSION HAD NOT ASSOSIATED TO THE ‎INCIDENCE OF OSTEOARTHRITIS IN BANJARBARU ‎INDONESIA - Oski Illiandri (Indonesian Journal for Health Sciences, 2021)
Hypertension has been known as one of the leading causes of death in Indonesia. Its major complications such as cerebrovascular accidents and heart disease are frequently associated with morbidity and disability. Recently, some research reports that hypertension had associated with the incidence of osteoarthritis. However, numerous researchers had disapproved of this theses and many research were conducted. To clarify this controversy, we conducted a small study to determine the relationship between the incidence of osteoarthritis in hypertensive patients. This study used an observational analytic study with a cross-sectional design. Purposive sampling method was used and obtain 50  peoples in Cempaka Health Centre of Banjarbaru chosen as the sample. Among them were 46 patients (92%) who had hypertension and 21 patients (42%) who had osteoarthritis. Hypertensive patients with osteoarthritis were 20 patients (40%), which is more than those without hypertension, as many as 1 patients (2%). Analysis using the fisher’s exact test obtained p=0.630 with a confidence level of 95%. Based on the research conducted it can be concluded that hypertension had not been associated with the incidence of osteoarthritis.